Propagation parameters of ultrasonic waves in polymer composites - RADZISZEWSKI, L. (Archives of Acoustics, 2000)
The non-contact ultrasonic technique of wave generation was used to test polymer composites. Transient elastic waves were generated with a Nd:YAG pulsed laser. Measurements aiming at the determination of the macroscopic parameters of propagation of bulk waves (amplitude, velocity and frequency distribution) were made in a unidirectional glass/epoxy (GFC) and isotropic polyvinyl chlorid plastic (PVC) thick plate. The influence of a constrained surface on the ultrasound parameters is discussed. The variations of the macroscopic parameters of propagation as functions of distance from the epicentrum were studied. PZT-ceramic standard ultrasound probes were used as receiver.